2012
DOI: 10.1097/ta.0b013e31824bde1e
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital trauma systems reduce mortality in developing countries

Abstract: Meta-analysis, level III+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(125 citation statements)
references
References 18 publications
4
115
2
4
Order By: Relevance
“…34 Pre-hospital time has been examined in various forms for other traumatic injuries in previous studies. 5,7,10,26 It has been shown thatfor high-velocity trauma -the earlier a patient receives initial treatment, the better the outcome. [34][35][36] The longest times from injury to admission occurred in hospital systems in low-income countries that did not have adequate resources available for the initiation of emergency medical services in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Pre-hospital time has been examined in various forms for other traumatic injuries in previous studies. 5,7,10,26 It has been shown thatfor high-velocity trauma -the earlier a patient receives initial treatment, the better the outcome. [34][35][36] The longest times from injury to admission occurred in hospital systems in low-income countries that did not have adequate resources available for the initiation of emergency medical services in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-hospital time has been reported as a valid quality indicator in other research articles but not specifically for patients with fractured femurs. 5,26 The admission to surgery interval is affected by in-hospital variables such as the availability of human resources and essential equipment and the hospital infrastructure. 27 The final surgery to discharge interval may be affected by medication availability, nursing care, rehabilitation and the postoperative availability of social services.…”
Section: Researchmentioning
confidence: 99%
“…5 Basic first aid administered at the scene of an injury has been shown to decrease morbidity and mortality. [7][8][9] The challenges presented by traumatic injuries are especially acute in South Sudan. The population exceeds 11 million people, 83% of whom live in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…With growing morbidity and mortality caused by non-communicable diseases and injuries in LMICs, emergency services, including pre-hospital care, are urgently required in order to prevent needless death and disability [5, 6]. Pre-hospital care is essential to achieving such a goal, as highlighted in a recent systematic review which showed that the availability of pre-hospital trauma systems in LMICs resulted in a 25% reduction in trauma-related mortality [7]. …”
Section: Introductionmentioning
confidence: 99%